Sinergi Pendidikan dan Kesehatan untuk Masyarakat Melalui Jalan Sehat di Nagari Kampung Tengah - Fahmarita Fahmarita; Fitri Handayani; Ghina Alya Dzakwan; Ira Safira; Nasya Aulia Ramadhani; Yasypi’i Pakhiri Caniago; Sandra Dewi (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This article aims to analyze the impact of the "Jalan Sehat" program as an effort to synergize education and health for the community in Nagari Kampung Tengah. This program is a collaborative initiative between educational institutions and communities designed to raise awareness of the importance of a healthy lifestyle and basic health education. The results showed that "Jalan Sehat" succeeded in increasing community participation in physical activity, reducing levels of physical inactivity, and strengthening knowledge and awareness of the importance of health. In addition, the program has strengthened the relationship between education and health institutions, creating an environment that supports continuous learning about health. Other positive impacts include increased social interaction and sense of community among community members. Overall, it can be concluded that health walk activities have great potential to effectively integrate aspects of education and health in the community, which in turn can improve the quality of life and well-being of the community.